Development of performance metrics for phase-based capital project benchmarking. Issue 3 (April 2016) - Yun, Sungmin; Choi, Jiyong; de Oliveira, Daniel P.; Mulva, Stephen P.
Abstract: Despite various research efforts focusing on the development of an effective measurement system, most project performance metrics were designed for post evaluation of processes and practices after project completion. This paper presents performance metrics tailored to phase-based benchmarking, which can be utilized as both leading and lagging indicators. Built upon industry experts' input and an extensive review of existing metrics, a framework for performance metrics was developed to evaluate performance outcomes for five major phases; front end planning/programming, design/engineering, procurement, construction, and startup/commissioning. Within this framework, phase-wise and phase-specific metrics were created under the categories of cost, schedule, efficiency, staffing, procurement, and safety performance. The results show that the framework and metrics are effective for the evaluation of project performance throughout capital project delivery. By employing the benchmarking process during the course of the project, industry practitioners can improve project performance and develop proactive strategies for subsequent phases. Highlights: This paper proposes performance metrics tailored to phase-based benchmarking for capital projects. Data normalization methods are suggested and discussed for proper application of performance metrics. Practical applicability of the proposed metrics is discussed for phase-specific and phase-wise performance assessment. The proposed performance metrics recognize vulnerable processes or practices, can be used for performance improvement.